(untitled) (Global Journal of Management and Business Research, 2020)
This study x-rayed the impact of pay as you earn on social and economic development (proxy by gross domestic products) in Nigeria. Secondary time series panel data was collected for the period 2009 to 2018 from the Statistical Bulletin of the Central Bank of Nigeria (CBN). The study employed Ordinary Least Squares (OLS) technique based on the computer software Eview 10 version for the analysis of data, where gross domestic products (GDP) is the independent variable, proxy for social and economic development, was regressed as a function of personal income tax (PIT) and value-added tax (VAT), the dependent variables.